2018
DOI: 10.1007/s10620-018-5251-9
|View full text |Cite|
|
Sign up to set email alerts
|

Hepatitis B Surface Antigen Loss with Tenofovir Disoproxil Fumarate Plus Peginterferon Alfa-2a: Week 120 Analysis

Abstract: Background and AimsHepatitis B surface antigen (HBsAg) loss is the ideal clinical endpoint but is achieved rarely during oral antiviral treatment. A current unmet need in CHB management is achievement of HBsAg loss with a finite course of oral antiviral therapy, thereby allowing discontinuation of treatment. Significantly higher rates of HBsAg loss at 72 weeks post-treatment have been demonstrated when tenofovir disoproxil fumarate (TDF) was combined with pegylated interferon (PEG-IFN) for 48 weeks compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 20 publications
5
38
0
Order By: Relevance
“…In Study 149, the HBeAg seroconversion rate was higher in HBeAg‐positive patients treated with peg‐IFN‐α plus TDF for 48 weeks than in those treated with TDF alone (25.0% vs 12.8%, respectively; P = 0.025) at week 72 (24 weeks after peg‐IFN‐α cessation). The cumulative rate of HBsAg loss at week 120 of follow‐up was significantly higher in patients (including both HBeAg‐positive and HBeAg‐negative patients) receiving combination therapy than in those receiving peg‐IFN‐α or TDF alone (10.4% vs 3.5% vs 0%, respectively; P < 0.001 and P = 0.002) …”
Section: Efficacy Of Peg‐ifnα−containing Regimens In Achieving a Funcmentioning
confidence: 98%
See 2 more Smart Citations
“…In Study 149, the HBeAg seroconversion rate was higher in HBeAg‐positive patients treated with peg‐IFN‐α plus TDF for 48 weeks than in those treated with TDF alone (25.0% vs 12.8%, respectively; P = 0.025) at week 72 (24 weeks after peg‐IFN‐α cessation). The cumulative rate of HBsAg loss at week 120 of follow‐up was significantly higher in patients (including both HBeAg‐positive and HBeAg‐negative patients) receiving combination therapy than in those receiving peg‐IFN‐α or TDF alone (10.4% vs 3.5% vs 0%, respectively; P < 0.001 and P = 0.002) …”
Section: Efficacy Of Peg‐ifnα−containing Regimens In Achieving a Funcmentioning
confidence: 98%
“…At week 72 of follow‐up when patients in the peg‐IFN‐α group had discontinued therapy for 24 weeks but patients in the TDF group were still on‐treatment, HBsAg loss was observed in 3.8% and 0% of patients, respectively. In an extended follow‐up analysis of Study 149 up to week 120, HBsAg loss was observed in 3.5% and 0% of patients (including both HBeAg‐positive and HBeAg‐negative patients) treated with peg‐IFN‐α and TDF monotherapy, respectively …”
Section: Efficacy Of Peg‐ifnα−containing Regimens In Achieving a Funcmentioning
confidence: 99%
See 1 more Smart Citation
“…A decline in HBsAg at week 12 or 24 of treatment was associated with HBsAg loss at week 72, while a decrease in HBsAg >3.5 log 10 IU/mL at week 24 identified HBsAg loss at week 72 in patients who completed a 48‐week course of Peg‐IFN+TDF (PPV = 85% and NPV = 99%) 3 . Follow‐up data at week 120 confirm the increased rate of HBsAg loss in patients treated with Peg‐IFN+TDF compared to those receiving either monotherapy (10.4% vs 3.5% in group B and D vs 0% in group C) 4 …”
Section: De Novo Peg‐ifn+nucs Combinationmentioning
confidence: 79%
“…A recent randomized controlled trial evaluating HBsAg loss in both HBeAg‐positive and HBeAg‐negative treatment‐naive patients showed that 48 weeks of combination therapy with TDF and Peg‐IFN led to a greater on‐treatment HBsAg decline at the end of treatment and a higher rate of HBsAg loss (9.1%) at 24 weeks post‐treatment than 16 weeks of combination therapy or either monotherapy alone, particularly in genotype A patients . At week 120, 10.4% of patients treated with combination therapy with TDF and Peg‐IFN for 48 weeks lost HBsAg . A recent study in 26 patients with HBV genotype C infection administered both ETV and Peg‐IFN simultaneously for 48 weeks showed that the 5‐year cumulative rate of HBsAg loss after the completion of combination therapy was 15% …”
Section: Treatment Strategies and Roadmapmentioning
confidence: 99%